Application of Positive Culture in Realizing the Character of Pancasila Student Profile for Elementary School - Eka Wati, Nita Nur; Utami, Ratnasari Diah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of writing this article is (1) to find out what positive culture has been implemented in Muhammadiyah 3 Surakarta Elementary School; (2) Efforts to apply positive culture in Muhammadiyah 3 Surakarta Elementary School to low-grade students in realizing the character of Pancasila student profiles; and (3) Factors that influence success in implementing a positive culture in SD Muhammadiyah 3 Surakarta. This study uses a qualitative method using a case study approach. Collecting data using interview techniques, observation, and documentation Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The subjects of this study were school principals, teachers, and students at SD Muhammadiyah 3 Surakarta. The results of this study indicate that SD Muhammadiyah 3 Surakarta has implemented a positive culture well. The positive culture that has been implemented is praying before and after learning activities, singing the national anthem following extracurricular activities, discussing during lessons, picketing together, doing community service at school, and making works of art. The efforts of SD Muhammadiyah 3 Surakarta teachers that have been implemented are building good relationships between students, making class agreements, implementing a culture of discipline, setting an example first and then applying it to their students, and getting used to it every day. Factors that influence success in implementing a positive culture are cooperation and participation among school members or within the school environment, community environment, and family environment.